Understanding Peer Effects: On the Nature, Estimation and Channels of Peer Effects - Jan Feld; Ulf Zölitz (Institute for the Study of Labor (IZA), 2015)
This paper estimates peer effects in a university context where students are randomly assigned to sections. While students benefit from better peers on average, low-achieving students are harmed by high-achieving peers. Analyzing students' course evaluations suggests that peer effects are driven by improved group interaction rather than adjustments in teachers' behavior or students' effort. We further show, building on Angrist (2014), that classical measurement error in a setting where group assignment is systematic can lead to substantial overestimation of peer effects. With random assignment, as is the case in our setting, estimates are only attenuated.
Keywords: I21; I24; J24; 330; estimation bias; measurement error; higher education; peer effects